Effect of the isocoumarin paepalantine on the luminol and lucigenin amplified chemiluminescence of rat neutrophils - Kitagawa, R. R.; Raddi, MSG; Khalil, N. M.; Vilegas, Wagner [UNESP]; da Fonseca, L. M. (Pharmaceutical Soc Japan, 2003)
Paepalantine (9,10-dihydroxy-5,7-dimethoxy-1H-naphto(2,3c)pyran-1-one), a natural isocoumarin isolated from the capitula of Paepalanthus bromelioides (Eriocaulaceae), was assessed for its effect on the respiratory burst (zymosan-stimulated luminol-enhanced chemiluminescence and. PMA-stimulated lucigenin-enhanced chemiluminescence) of polymorphonuclear neutrophils in vitro. Special attention was devoted to establishing the IC50 for neutrophils. Paepalantine was able to decrease luminol and lucigenin chemiluminescence, reflecting an inhibitory effect on the respiratory burst, with an ED50 of 0.44 +/- 0.05 and 0.84 +/- 0.15 mug/ml, respectively. A cell-free system was performed with paepalantine on myeloperoxidase/H2O2 and myeloperoxidase/H2O2/Cl- systems. Paepalantine inhibited luminol oxidation in both systems. This inhibition was related to the interaction of paepalantine-myeloperoxidase and its scavenger effect on HOCl.
Keywords: antioxidant activity; paepalantine; isocoumarin; chemiluminescence